Needs assessment: strategies for raising awareness of construction management programs among high school counselors - Wilkes, Jeffrey T., author; Nobe, MaryEllen C., advisor; Clevenger, Caroline M., committee member; Cross, Jennifer E., committee member (Colorado State University. Libraries, 2014)
High school students comprise a high percentage of prospective students entering Construction Management (CM) departments. High school counselors are in a unique position to impart significant influence on these students as they make decisions about attending college. This is significant to CM departments because it has been observed by department advisors that high school counselors do not heavily influence current CM student's decisions to pursue a CM degree. The authors performed a needs assessment to test the accuracy of this observation, determine counselor's knowledge and perceptions of CM, and determine strategies for raising awareness. Phase I of the needs assessment surveyed first semester CM students to determine if counselors played a significant role in their decision to pursue a CM degree. The results revealed that students were meeting with their counselor for advice, but few reported the counselor influenced their decision. This confirmed the need to further explore the high school counselor's knowledge and perceptions of CM. Phase II of the needs assessment surveyed high school counselors in the state of Colorado. The results show that counselors do not possess a high level of knowledge regarding CM degrees and careers, but also shows that they would be willing to learn more if the right information and training opportunities were provided to them. The results also highlight the counselor's barriers to learning more about CM, namely lack of available information, lack of time, lack of training opportunities, and lack of student interest. In Phase III of the needs assessment, the High School Counselor Outreach Program (HSCOP) was developed with the specific goal of raising counselor's knowledge of CM programs. The HSCOP was specifically developed to address the counselor's need while respecting the barriers reported in Phase II. This two stage program closes the counselor's CM knowledge gap by giving CM departments an outline to provide targeted information packages to counselors in Stage 1 and accessible training opportunities in Stage 2.
Keywords: construction management; student recruitment; high school counselor